2021
DOI: 10.3389/fpubh.2021.647725
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of 23-Valent Pneumococcal Polysaccharide Vaccine Program for the Elderly Aged 60 Years or Older in Shanghai, China

Abstract: Background: The pneumococcal vaccine has been considered as the most effective measure to prevent pneumococcal diseases. In 2013, Shanghai launched a major public health program to vaccinate people aged 60 years or older with 23-Valent Pneumococcal Polysaccharide Vaccine (PPSV-23) free of charge. By the end of June 2020, a total of 1.56 million old people had been vaccinated free of charge.Objective: To evaluate the cost-effectiveness of PPSV-23 vaccination program in Shanghai from the health system perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A total of 1.56 million elderly population were vaccinated through this program with an estimated coverage of 30%. 22 …”
Section: Vaccination Coverage Of Pneumococcal Vaccines Among Elderly ...mentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 1.56 million elderly population were vaccinated through this program with an estimated coverage of 30%. 22 …”
Section: Vaccination Coverage Of Pneumococcal Vaccines Among Elderly ...mentioning
confidence: 99%
“…Shanghai has implemented a policy to provide free vaccine to residents with 60 years or old with PPSV-23 since 2013 which lead to increased vaccination rate (1.56 million people were vaccinated). 10 , 22 A questionnaire survey among the elderly residents (aged 50–69 years) in 13 communities in Shanghai in 2020 reported that price sensitivity plays a key role in acceptance of PPSV-23 vaccination. Vaccination willingness was 79.4% (free PPSV-23 for local persons), 54.7% (self-paid PPV23 for non-local persons).…”
Section: Factors Influencing the Pneumococcal Vaccination Among Elderlymentioning
confidence: 99%
See 2 more Smart Citations